2012
DOI: 10.1093/neuonc/nos004
|View full text |Cite
|
Sign up to set email alerts
|

Upfront association of carboplatin plus pemetrexed in patients with brain metastases of lung adenocarcinoma

Abstract: Approximately 10% of patients with non-small cell lung cancer (NSCLC) have brain metastases at the time of diagnosis. When surgical resection is not possible, whole brain radiotherapy is the standard of care, with a cerebral response rate of approximately 30%. We report our experience with an upfront association of carboplatin and pemetrexed (areas under the curve, 5 and 500 mg/m 2 , respectively), every 3 weeks, in 30 patients presenting with newly diagnosed brain metastases and NSCLC. Cerebral MRIs were perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
44
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(47 citation statements)
references
References 30 publications
1
44
0
2
Order By: Relevance
“…The median OS time was 10 months. The results of these three studies indicate that pemetrexed is a good treatment option in such patients (29)(30)(31).…”
Section: Actuarial Survival (%) -------------------------------------mentioning
confidence: 94%
See 2 more Smart Citations
“…The median OS time was 10 months. The results of these three studies indicate that pemetrexed is a good treatment option in such patients (29)(30)(31).…”
Section: Actuarial Survival (%) -------------------------------------mentioning
confidence: 94%
“…For pemetrexed, data regarding patients with BM have been published in the first-and second-line settings. A response rate of 40% for newly diagnosed BM was reported by Bailon et al (2012) (29) in 30 patients with non-squamous NSCLC following first-line therapy with pemetrexed plus carboplatin. The median OS time was 39 weeks (29).…”
Section: Actuarial Survival (%) -------------------------------------mentioning
confidence: 99%
See 1 more Smart Citation
“…This phenomenon could support the use of upfront chemotherapy for BM that damage the integrity of the barrier (15,16). First line upfront platinum based chemotherapy has been evaluated in different prospective trials and an objective response rate (ORR) of 23-50% was reported (5,(17)(18)(19)(20)(21)(22)(23)(24). Pemetrexed and temozolomide showed some activity (25-29) while 5-FU, topotecan and vinorelbine, did not show any improvement in ORR and OS (23,30,31).…”
mentioning
confidence: 91%
“…However, most patients die from systemic disease rather than intracranial failure. Systemic treatment with novel agents, such as tyrosine kinase inhibitors (TKIs) and pemetrexed, has been shown to be beneficial in patients with BM [14][15][16][17][18]. They could not only shrink the intracranial lesions, but also prolong the survival.…”
Section: Introductionmentioning
confidence: 99%